(untitled) (Sir Salimullah Medical College Journal, 2022)
Objectives: The present study was designed to find out the bacterial causes of conjunctivitis among neonates and under five children and their antibiotic sensitivity pattern. Methodology: A cross sectional study was done in the department of Microbiology, Dhaka Medical College from July 2012 to June 2013. Conjunctival swab samples were collected from neonates and children of clinically suspected conjunctivitis attending OPD of Dhaka Medical College Hospital and National Institute of Ophthalmology and Hospital. Results: Out of 206 cases, 145 (70.73%) were culture positives. Most common gram positive bacteria was Staphylococcas aureus and gram negative bacteria was Pseudomonas aeruginosa. In neonates, Chlamydia trachomatis were detected by PCR. Organisms show highest sensitivity to vancomycin, amikacin, and chloramphenicol. Conclusion: So, early diagnosis of bacterial causes and its antibiotic sensitivity pattern will help in proper management of childhood conjunctivitis. Sir Salimullah Med Coll J 2022; 30: 123-128